Investigation of the Mechanical Properties of Flax Cell Walls during Plant Development: The Relation between Performance and Cell Wall Structure - Goudenhooft, Camille; Siniscalco, David; Arnould, Olivier; Bourmaud, Alain; Sire, Olivier; Gorshkova, Tatyana; Baley, Christophe (Fibers, 2018)
The development of flax (Linum usitatissimum L.) fibers was studied to obtain better insight on the progression of their high mechanical performances during plant growth. Fibers at two steps of plant development were studied, namely the end of the fast growth period and at plant maturity, each time at three plant heights. The indentation modulus of the fiber cell wall was characterized by atomic force microscopy (AFM) using peak-force quantitative nano-mechanical property mapping (PF-QNM). Changes in the cell wall modulus with the cell wall thickening were highlighted. For growing plants, fibers from top and middle heights show a loose inner Gn layer with a lower indentation modulus than mature fibers, which exhibit thickened homogeneous cell walls made only of a G layer. The influence of these changes in the fiber cell wall on the mechanical performances of extracted elementary fibers was also emphasized by tensile tests. In addition, Raman spectra were recorded on samples from both growing and mature plants. The results suggest that, for the fiber cell wall, the cellulose contribution increases with fiber maturity, leading to a greater cell wall modulus of flax fibers.